(untitled) (World of finance, 2019)
Introduction. The unstable political, economic and social realities in the state, crisis phenomena, as well as new strategies for change determine the direction of further development of the fiscal component of the customs security of the state. At the present stage of the intensive entry into the foreign economic space in the European direction, the important role belongs to the maximum approach to European customs security standards of Ukraine. The purpose of the article is to diagnose the functioning of the fiscal component of customs security and to carry out a thorough analysis of its provision in Ukraine, which undoubtedly has a significant impact on the formation of effective areas for reforming the customs system. Results. The article analyzes the system of indicators for the provision of customs security in Ukraine. The functioning of the fiscal component of customs security and a thorough analysis of its provision in Ukraine are explored, which certainly has a significant impact on the formation of effective areas for reforming the customs system. Conclusion. It should be noted that under the effectiveness of customs security it is necessary to understand the indicator, which reflects the ratio of results of activity in the relevant field and involved in achieving such results of resources.